2013
DOI: 10.1111/tra.12074
|View full text |Cite
|
Sign up to set email alerts
|

Different Munc13 Isoforms Function as Priming Factors in Lytic Granule Release from Murine Cytotoxic T Lymphocytes

Abstract: In order to fuse lytic granules (LGs) with the plasma membrane at the immunological synapse, cytotoxic T lymphocytes (CTLs) have to render these LGs fusioncompetent through the priming process. In secretory tissues such as brain and neuroendocrine glands, this process is mediated by members of the Munc13 protein family. In human CTLs, mutations in the Munc13-4 gene cause a severe loss in killing efficiency, resulting in familial hemophagocytic lymphohistiocytosis type 3, suggesting a similar role of other Munc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Our finding that Munc13-4 is required for immobilizing dense granules offers new insights into the mechanisms of dense granule exocytosis and suggests that they exist in a “docked/tethered” state that is poised for release. This mechanism appears to be similarly used for lytic granules in cytotoxic T lymphocytes were loss of Munc13s increases granule mobility (57). Our data also account for the robust bleeding and hemostasis defect observed in the Unc13d Jinx mice that lack the protein (24, 26, 58, 59) and are congruent with the phenotype observed in humans harboring mutations in UNC13D , the human homologue of Munc13-4 (60, 61).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that Munc13-4 is required for immobilizing dense granules offers new insights into the mechanisms of dense granule exocytosis and suggests that they exist in a “docked/tethered” state that is poised for release. This mechanism appears to be similarly used for lytic granules in cytotoxic T lymphocytes were loss of Munc13s increases granule mobility (57). Our data also account for the robust bleeding and hemostasis defect observed in the Unc13d Jinx mice that lack the protein (24, 26, 58, 59) and are congruent with the phenotype observed in humans harboring mutations in UNC13D , the human homologue of Munc13-4 (60, 61).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Munc13-4 is involved in regulated exocytosis in hematopoietic secretory cells, such as cytotoxic T lymphocytes (CTLs), platelets, neutrophils, and mast cells (7,12,27,30,33,35). It is also known that in neurons, chromaffin cells, and CTLs, multiple Munc13 isoforms are endogenously expressed, and play some redundant roles in the promotion of the docking and priming of secretory vesicles/granules (8,10,24,36). In mast cells, Munc13-4 is shown to be crucial for degranulation (11,35,38); however, the involvement of other Munc13 isoform(s) still remains unknown.…”
Section: Rt-pcr and Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…Upon multivesicular exocytosis in mast cells, late and recycling endosomes have been shown to fuse sequentially with the growing exocytic structures formed by Munc13-4-dependent SG-SG fusion (SG-derived exocytic structures) (38). Because the SGs in the mast cells themselves possess endosomal properties, especially those of late endo-DISCUSSION Munc13-1 has been recently found to be expressed together with Munc13-4 in CTLs, and both the proteins have been shown to positively regulate the priming process in lytic granule exocytosis, indicating their functional overlap (10). In the present study, we showed that Munc13-1, as well as Munc13-4, is endogenously expressed in the RBL-2H3 mast cell line; however, unexpectedly, we found that in contrast to its effect on CTLs, Munc13-1 inhibited the antigen-induced degranulation of the RBL-2H3 cells.…”
Section: Functional Relationship Between Munc13-1 and Munc13-4mentioning
confidence: 99%
“…The green dot represents the starting position of the LG and the red dot represents the end position of the LG. The absence of the priming factor Munc13-4 leads to a significant increase in vesicle mobility in TIRFM (28). (C) Fluorescence profile of a fusing LG (left), a stationary LG (middle), and an LG that is undocking (right) as seen in TIRFM.…”
Section: Visualizing and Quantifying Lytic Granules At The Is By Tirfmmentioning
confidence: 99%